LEGAL ASPECTS OF IMPLEMENTATION OF ADDITIONAL EMPLOYEE INCOME FOR STATE CIVIL APPARENTS IN MAKASSAR HEALTH SECTOR - Arsita, Rezky; Bachri, Syamsul; Riza, Marwati (Program Pascasarjana, UIN Alauddin Makassar, 2022)
The provision of TPP is to improve employee welfare and satisfaction with the performance benefits of ASN employees. However, in Makassar there is an exception for the provision of TPP ASN for health workers which results in discrimination for health workers. Thus, the author is interested in studying the implementation of Perwali Number 58 of 2020, the mandate of the Minister of Home Affairs Number 061-5449 of 2019 concerning the Procedure for Approval of the Minister of Home Affairs on the TPP ASN in the scope of the Regional Government. This study used an empirical approach to legislation (Statute Approach) commonly known as the juridical-normative approach. This research also used a conceptual approach which is a type of legal research that provides an analytical point of view on solving a problem from the aspect of legal concepts. The results of the analysis from this study state that the implementation of Perwali Number 69 of 2020 accommodates the provision of TPP for Health workers and is in accordance with the laws and regulations as the legal basis for implementing PP Number 12 of 2019 concerning Regional Financial Management. However, it is still limited because it is only managed in certain agencies, namely only at the Health Office, not to the UPT Hospitals and Public Health Center due to several components, namely workload and work performance not being met, the existence of medical services, and regional financial capabilities. So that there is a need for coordination and optimization of increasing effectiveness regarding the elements of the tested criteria for providing TPP.